Laparoscopic resection of small bowel gist: a case report - Mark, Satkunan; Wai, Lai Weng; Supramaniam, Navien; Wai, Yan Yang (International Surgery Journal, 2021)
Small bowel bleed accounts for approximately 5% of all gastrointestinal bleeding. While arteriovenous malformation is the commonest cause of small bowel bleeding, other causes include inflammatory bowel disease, small bowel tumours, ulcers and polyps make up the rest. Tumours range from benign adenomas, hamartomas and leiomyomas to malignant GISTs, adenocarcinomas or lymphomas. We reported a case of a jejunal GIST causing intermittent bleeding. Upper and lower GI endoscopy did not find any abnormality and the diagnosis was made through computerized tomography. It showed a mid-jejunal tumour that was in close proximity to the distal duodenum. The rest of the hollow and solid organs were normal. The patient was prepared and underwent laparoscopic assessment. The tumour was mobile, arising from proximal jejunum and did not show infiltration or adhesions to nearby viscera. A segmental resection with adequate margin was performed laparoscopically and extracted through the umbilical port wound. The pathology report revealed an intermediate GIST with clear margins. Laparoscopic assessment should ideally be carried prior to any resection of small bowel tumours. Uncomplicated small bowel resections can safely be done laparoscopically with good oncological outcome and faster patient recovery.